Bioefficacy of some biorational insecticides for the control of Aphis gossypii Glover, 1877, (Hemiptera: Aphididae) on greenhouse grown cucumber - Mohammad Saeed Emami (Acta Agriculturae Slovenica)
Aphis gossypii Glover, 1877 is a serious pest of cucumber in greenhouse plantings. Biorational insecticides are an alternative of broad spectrum insecticides for aphid suppression in greenhouse. In this regards, the efficiency of some biorational insecticides including soap based on coconut oil, surfactant based on sodium sulfosuccinate and antifeeding based on potassium nicotinate were assayed on A. gossypii in the cucumber greenhouse. The trials were set up in a randomized complete block design with four replications. Samplings were carried out one day before spraying and 3, 7, 14 and 21 days after spraying. The data were submitted to ANOVA and the means comparison was performed using Duncan’s test. The results indicated that the highest mortality in insecticidal soap, surfactant and antifeeding treatments occurred after 3 days, with 78.47 %, 67.16 % and 60.48 % mortality, respectively. The results of the trials are discussed in terms of improving management of the populations of A. gossypii.